3D Slot Roughness Evaluation Of Novel Orthodontic Brackets With Two Commercial Brackets (An İn-Vitro Study) - Omar Sabah; Isra Dilshad; Sana Rizgar (Eurasian Journal of Science and Engineering)
The purpose of the study is to evaluate the roughness of the new E-max brackets with two commercially available ceramic brackets in the markets. The bracket roughness of three different types was compared. The brackets were divided into three groups: (1) E-max brackets (IPS E-max press, Ivoclar, Germany), (2) Gemini clear brackets (Unitek, 3M, USA), and (3) Discovery pearl ceramic brackets (Dentaurum, Germany). The roughness of each bracket was tested through a 3D laser microscope (VK-X1100, Keyence, Germany). The Gemini clear showed a uniform surface significantly smoother than both E-max and Discovery pearl brackets with the latter having the highest roughness parameter. As a result of the noticeable tested brackets, E-max material is now and will continue to be a common choice for modern, aesthetically pleasing brackets, despite having a rougher surface than Gemini Clear but less than Discovery Pearl. To reduce roughness, the E-max brackets could benefit from better polishing and finishing. Hence, to lessen friction.